(untitled) (Caderno Espaço Feminino, 2017)
Resumo O interesse pela análise das ações sociais das Moças das Tranças na "Praça Nova" nasce com o intuito de expandir a discussão sobre as (re)significações das tranças e outros penteados em Angola. EÌ evidenciada a presença do gênero feminino e a relação deste na praça e com a praça, instituição fundamental no país que é lugar, não apenas de compra e venda, mas também de socialização e permané‚ncia. Palavras-chave: Moças das Tranças. Praça. Relações Sociais. Abstract The interest in analyzing the social actions of the Braid Women at "Praça Nova" comes on light with the purpose of expending the discussion about the (re)significations of braids and other hairstyles in Angola. It is evidenced the presence of the female gender and its relation in and with the praça, a fundamental institution in the country which is a place, not only for trade, but also for socialization and permanence. Keywords: Braid Women. Praça. Social RelationsÂ